Sistem Informasi Peminjaman Fasilitas Barang Untuk Proses Belajar Mengajar Menggunakan Barcode Berbasis Web - Hendrawaty, Muhammad Sural Fuadi, Azhar (Jurnal Elektro dan Informatika, 2021)
Data collection on loan facilities at the Teaching and Learning Process is an important activity as a means of borrowing documentation at the Informatics Engineering Study Program at the State Polytechnic in Lhokseumawe. The process of borrowing Goods Facilities at the Informatics Engineering Study Program in its implementation is still done manually by means of the borrowers coming to the Study Room by writing down the data of the borrowers themselves. Then, in the case of recording loan items, it is also done manually by means of the borrower manually recording items that he wants to borrow in a book, the borrower must also go directly to the study program to check whether the items to be borrowed are still available or not. Today technology has grown rapidly. One of them is the labeling technology that is widely used today with Barcode. The aim is to automate the system of inputting and checking borrower data and borrowed goods at the Informatics Engineering Study Program. Information System for Lending Property Facilities at Web Based Informatics Engineering Study Program Using Barcode as a medium to obtain borrower data and borrowed goods information. This system is made to improve the existing manual system to be computerized so that it can be made through desktop or mobile and can provide complete and efficient lending information stored in a database server. This system displays output in the form of printed barcode products and loan data that can be printed. In addition, study program staff and borrowers will get notification of return information when the return time for goods has arrived.